Workshop of Technology-Based Mathematics Teaching Materials for Vocational High School Teachers - Retno Marsitin; Nyamik Sesanti (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The development of technology in the digital era 4.0 has an impact on education so that teachers are required to be able to apply technology in teaching. One of the efforts is by providing training about technology-based mathematics teaching materials for vocational high school teachers. The training activity is a community partnership program that aims to improve Vocational High School teachers’ understanding in creating technology-based mathematics teaching materials and improve vocational high School teachers’ skills in creating technology-based mathematics teaching materials. The method of implementing this community partnership program is in the form of workshop which include giving technology-based mathematics teaching materials, installing applications, applying technology-based mathematics teaching materials, interactive dialogue with presentation simulations, and evaluations as achievement indicators of the implementation of the community partnership program. The results of the community partnership program are in the form of technology-based mathematics teaching materials in mathematics learning. The results achieved are the improvement of Vocational High School teachers’ understanding in creating technology-based mathematics teaching materials and improvement of Vocational High School teachers’ ability in creating technology-based mathematics teaching materials